Investigation and experiment of data acquisition and wireless transmission board for wearable application - Yap, Jason Wei Han (Nanyang Technological University, 2020)
Cardiovascular disease refers to situation that blocked or narrowed the blood vessel which lead to a heart attack, stroke and chest pain [1]. Cardio disease is commonly known as the leading cause of death. According to the statistics from Singapore Heart Foundation, an amount of 17 people dies from cardiovascular disease in Singapore every day. This disease accounted for 29.2% of all deaths in 2018 and this implies that almost 1 out of 3 deaths in Singapore, is due to heart diseases or stroke [2]. Thus far, there has been a considerable amount of research to prevent cardiovascular disease conducted worldwide [3]. Although the primary way to tackle this disease is to change the diet and exercise regularly, the wearable data is also able to help in preventing heart disease. Associate Professor Yeo Khung Keong, Senior Consultant at NHCS’ Department of Cardiology suggested that wearable sensors may play a significant role in aiding the diagnosis of heart conditions in the future [4]. Numerous wearable devices like smart watch have been manufactured since then to prevent this disease. However, the issue here is that the risk of getting cardio disease increases as the age, most of these devices are not available to those senior age group due to the high selling price. High power consumption and low battery storage require these devices to be charged regularly. Besides that, these devices normally can only be connected to personal devices that restricted the shareability of the data within house members. Another disadvantage possessed by fitness watch is the complicated user interface that restrict elderly to apply them. Therefore, it is important to come out with a wearable device that is lower cost, low power consumption which have a longer usage time, easy to connect and use by all age of people. The aim of this project was to learn and design a wearable device that can acquire data through body sensor and transmit the important data to different devices wirelessly. A flexible PCB board was designed to suite the application. Different testing and debugging process were also done to ensure the reliability and stability of the device designed. The significant of this project is to provide a device that is affordable to different age groups and directly help in preventing the cardiovascular disease to become the causes of death.